EDUCATION ENTREPRENEURSHIP, SELF-EFFICATION AND FAMILY ENVIRONMENT ON THE SPIRIT OF STUDENTS BUSINESS ENTREPRENEURS TROUGH PERSONALITY - dewi urip wahyuni; Rismawati Rismawati (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
This study aims to determine the effect of entrepreneurship education, self-efficacy and family environment on entrepreneurial spirit through personality. This research is a quantitative study using an approachcluster proportional sampling with primary data by distributing questionnaires to vocational high school students in Surabaya. The number of samples in this study were 180 vocational students. The data analysis method uses SEM. The results showed that entrepreneurship education influences entrepreneurial personality, self-efficacy influences entrepreneurial personality, family environment influences entrepreneurial personality, entrepreneurship education influences entrepreneurial spirit, self-efficacy influences entrepreneurial spirit, family environment influences entrepreneurial personality and entrepreneurial personality influences entrepreneurial spirit entrepreneurship.